A rare case report of ambiguous genitalia - LU, Chirag; Kumbar, Lohit; Selvan, Chitra; PR, Manjunath (Indian Journal of Child Health, 2024)
An ambiguous genitalia is a commonly referred clinical scenario to endocrinology outpatient department. Accurate diagnosis is paramount to prevent associated salt-wasting crisis, direct the gender of rearing in the short-term, and monitoring for the development of malignancy in the gonads in the long-term. 17 beta-hydroxysteroid dehydrogenase 3 deficiency (17 β HSD 3) is one of the causes of defective testosterone biosynthesis. 17β-HSD3 deficiency should be suspected in children with female external genitalia with inguinal hernias or mild clitoromegaly; as well as males with ambiguous genitalia who develop virilization and gynecomastia at puberty. A hormonal evaluation may not always be diagnostic which makes genetic confirmation essential.